Inducible Tertiary Lymphoid Structures: Promise and Challenges for Translating a New Class of Immunotherapy - Aoyama, Shota; Nakagawa, Ryosuke; Mulé, James J.; Mailloux, Adam W. (Frontiers in Immunology, 2021)
Tertiary lymphoid structures (TLS) are ectopically formed aggregates of organized lymphocytes and antigen-presenting cells that occur in solid tissues as part of a chronic inflammation response. Sharing structural and functional characteristics with conventional secondary lymphoid organs (SLO) including discrete T cell zones, B cell zones, marginal zones with antigen presenting cells, reticular stromal networks, and high endothelial venues (HEV), TLS are prominent centers of antigen presentation and adaptive immune activation within the periphery. TLS also share analogous signaling axes and leukocyte recruitment schemes with SLO regarding their formation. In cancer, their presence confers positive prognostic value across a wide spectrum of indications, spurring interest in their artificial induction as either a new form of immunotherapy, or as a means to augment other existing cell or immunotherapies. Here, we review approaches for inducible (iTLS) that utilize chemokines, inflammatory factors, or cellular analogues vital to conventional SLO organogenesis. This review also addresses biomaterials that have been or might be suitable for iTLS, and discusses remaining challenges facing iTLS manufacturing approaches for clinical translation.